The present and future aspects of the Common Agricultural Policy, the Polish position - Krzyżanowski, Julian (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2008)
The paper deals with the future of the EU Common Agricultural Policy. The New Financial Perspective (2007-2013) is being discussed. The paper is supplemented by analysis of the impact of the 2003 reform on the most important markets. Final part of the paper deals with a presentation of Poland’s position with regard to the future of CAP.